Is the age of diagnosis of esophageal adenocarcinoma getting younger? Analysis at a tertiary care center. Issue 9 (12th February 2020) - Strauss, Alexandra; Min, Eun Jeong; Long, Qi; Gabriel, Peter; Yang, Yu-Xiao; Falk, Gary W
Summary: There are emerging data that patients <50 years are diagnosed with esophageal adenocarcinoma (EAC) more frequently, suggesting that the age threshold for screening should be revisited. This study aimed to determine the age distribution, outcomes, and clinical features of EAC over time. The pathology database at the Hospital of the University of Pennsylvania was reviewed from 1991 to 2018. The electronic health records and pathology were reviewed for age of diagnosis, pathology grade, race, and gender for a cohort of 630 patients with biopsy proven EAC. For the patients diagnosed from 2009 to 2018, the Penn Abramson Cancer Center Registry was reviewed for survival and TNM stage. Of the 630 patients, 10.3% (65 patients) were <50 years old [median 43 years, range 16–49]. There was no increase in the number of patients <50 years diagnosed with EAC ( R  = 0.133, P  = 0.05). Characteristics of those <50 years versus >50 years showed no difference in tumor grade. Among the 179 eligible patients in the cancer registry, there was no significant difference in clinical or pathological stage for patients <50 years ( P value = 0.18). There was no association between diagnosis age and survival ( P  = 0.24). A substantial subset of patients with EAC is diagnosed at <50 years. There was no increasing trend of EAC in younger cohorts from 1991 to 2018. We could not identify more advanced stage tumors in the younger cohort. There was no significant association between diagnosis age and survival.